Extending the BEM for Elastic Contact Problems Beyond the Half-Space Approach - Zhao, Jing; Vollebregt, Edwin A.H.; Oosterlee, Cornelis W. (Mathematical Modelling and Analysis, 2016)
The boundary element method (BEM) is widely used in fast numerical solvers for concentrated elastic contact problems arising from the wheel-rail contact in the railway industry. In this paper we extend the range of applicability of BEM by computing the influence coefficients (ICs) numerically. These ICs represent the Green’s function of the problem, i.e. the surface deformation due to unit loads. They are not analytically available when the half-space is invalid, for instance in conformal contact. An elastic model is proposed to compute these ICs numerically, by the finite element method (FEM). We present a detailed investigation to find proper strategies of FEM meshing and element types, considering accuracy and computational cost. Moreover, the effects of computed ICs to contact solutions are examined for a Cattaneo shift contact problem. The work in this paper provides a guidance to study fast solvers for the conformal contact.